Adapted colorimetric method for measurement of feline urinary glycosaminoglycans - Pereira, Marcy Lancia [UNESP]; Pizauro Jr., João Martins [UNESP]; Carvalho, Marileda Bonafim [UNESP] (Springer Nature, 2012)
Several methods have been employed to quantify urinary glycosaminoglycans (GAGs), such as chromatography associated with electrophoresis and colorimetric methods, cheaper and faster ones, which employ mainly azure A and B, alcian blue, and dimethylmethylene blue (DMB). The purpose of this study was to standardize a reproducible and cheap method to measure total urinary GAGs in feline urine. Two colorimetric methods based on DMB were tested with chondroitin sulfate C as standard. Urine samples were obtained from 12 healthy cats and some modifications were made for the chosen method to be adequate. The modified technique using DMB acetate buffer carried out in this study can be used to measure feline urinary GAGs. © 2012 Springer-Verlag London.
Keywords: Cat; DMB; Glycosaminoglycan; Quantification; Urine